\begin{gathered}ax-4ax+4a=a\, (x-4x+4)=a\, (4-3x)-6a^2+12ab-6b^2=-6\, (a^2-2ab+b^2)=-6\, (a-b)^2-2x^2-8x-8=-2\, (x^2+4x+4)=-2\, (x+2)^2\end{gathered}ax−4ax+4a=a(x−4x+4)=a(4−3x)−6a2+12ab−6b2=−6(a2−2ab+b2)=−6(a−b)2−2x2−8x−8=−2(x2+4x+4)=−2(x+2)2
Объяснение:
можно лайк и корону
\begin{gathered}ax-4ax+4a=a\, (x-4x+4)=a\, (4-3x)-6a^2+12ab-6b^2=-6\, (a^2-2ab+b^2)=-6\, (a-b)^2-2x^2-8x-8=-2\, (x^2+4x+4)=-2\, (x+2)^2\end{gathered}ax−4ax+4a=a(x−4x+4)=a(4−3x)−6a2+12ab−6b2=−6(a2−2ab+b2)=−6(a−b)2−2x2−8x−8=−2(x2+4x+4)=−2(x+2)2
Объяснение:
можно лайк и корону